The Application of Lexical Retrieval Training in Tablet-Based Speech-Language Intervention - Gallée, Jeanne; Pittmann, Rachel; Pennington, Suzanne; Vallila-Rohter, Sofia (Frontiers in Neurology, 2020)
In the setting of shortened hospitalization periods, periods of confinement and social isolation, limited resources and accessibility, technology can be leveraged to enhance opportunities for rehabilitative care (Rutledge et al., 2014). In the current manuscript, we focus on the use of tablet-based rehabilitation for individuals with aphasia, a language disorder that frequently arises post-stroke. Aphasia treatment that targets naming through effortful and errorful instances of lexical retrieval, where corrective feedback is generated on every trial, may enhance retention and generalizability of gains (Middleton et al., 2015; Middleton et al., 2016). This pilot evaluation explored how six individuals with aphasia interacted with a tablet-based therapy application that targeted lexical retrieval. Participants with aphasia either (1) autonomously engaged with the therapy tasks or (2) received systematic encouragement to effortfully retrieve words. Behaviors of response latency and cue use were examined to gain insights into the behavioral patterns of both groups, as well as analyses of task accuracy and outcomes on standardized cognitive-linguistic assessments. Despite some variability, initial observations suggest that participants who received systematic training refrained from using cues to complete tasks and spent longer on each trial, which ultimately correlated with increased independent engagement with therapy and improved standardized outcomes. Preliminary results present an alternative means of leveraging technology to implement best-practice recommendations in the context of aphasia telerehabilitation.